2008
DOI: 10.1080/09540100802100202
|View full text |Cite
|
Sign up to set email alerts
|

Detection of grouper mislabelling in the fish market by an immunostick colorimetric ELISA assay

Abstract: We have applied an immunostick colorimetric enzyme-linked immunosorbent assay (ELISA) assay for the rapid authentication of grouper (Epinephelus marginatus) fillets in the fish market. An indirect ELISA has been assayed by using a monoclonal antibody (3D12) developed previously in another work. In this study, 52 commercial fish fillets samples collected from local markets and supermarkets, which were labelled as grouper, have been analysed by this methodology; only 14 samples were confirmed to be grouper. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 15 publications
(17 reference statements)
0
2
0
1
Order By: Relevance
“…The detection of allergenic fish residues in foods is of particular interest for Electrophoretic techniques, with isoelectric focusing being the most frequently used method, separate the sarcoplasmic proteins by their electrical charge differences and identifies the fish species based on the species-specific banding patterns of the whole proteins or parvalbumins (Esteve-Romero et al, 1996;Civera, 2003). Immunoassays like ELISA, on the other hand, uses either monoclonal or polyclonal antibodies against the soluble muscle proteins of specific fish species with no cross-reactivity to unrelated fish species to discriminate between the different species of fish (Huang et al, 1995;Carrera et al, 1996;Asensio et al, 2003Asensio et al, , 2008. PCR-based methods involve amplification of the DNA regions of interest that are universal or species-specific, followed by the analysis of the PCR fragments for species recognition using various methods, including electrophoretic techniques, DNA sequencing, restriction fragment length polymorphism (RFLP), single-stranded conformational polymorphism (SSCP), and many others (Gil, 2007;Rasamussen and Morrissey, 2008;Sun et al, 2009).…”
Section: Detection Methods For Fishmentioning
confidence: 99%
“…The detection of allergenic fish residues in foods is of particular interest for Electrophoretic techniques, with isoelectric focusing being the most frequently used method, separate the sarcoplasmic proteins by their electrical charge differences and identifies the fish species based on the species-specific banding patterns of the whole proteins or parvalbumins (Esteve-Romero et al, 1996;Civera, 2003). Immunoassays like ELISA, on the other hand, uses either monoclonal or polyclonal antibodies against the soluble muscle proteins of specific fish species with no cross-reactivity to unrelated fish species to discriminate between the different species of fish (Huang et al, 1995;Carrera et al, 1996;Asensio et al, 2003Asensio et al, , 2008. PCR-based methods involve amplification of the DNA regions of interest that are universal or species-specific, followed by the analysis of the PCR fragments for species recognition using various methods, including electrophoretic techniques, DNA sequencing, restriction fragment length polymorphism (RFLP), single-stranded conformational polymorphism (SSCP), and many others (Gil, 2007;Rasamussen and Morrissey, 2008;Sun et al, 2009).…”
Section: Detection Methods For Fishmentioning
confidence: 99%
“…Grouper, an expensive, highly appreciated, and highly demanded meat, is often substituted with lower-value fish species like Nile perch or wreck fish (Asensio et al, 2008). Asensio et al (2008) designed and tested an assay on 70 samples of commercial fish fillets and found that 58 of them were mislabeled. In their study, 34/70 samples of Nile perch and 13/70 wreck fish samples were mislabeled (Asensio et al, 2008).…”
Section: Perciformesmentioning
confidence: 99%
“…Asensio et al (2008) designed and tested an assay on 70 samples of commercial fish fillets and found that 58 of them were mislabeled. In their study, 34/70 samples of Nile perch and 13/70 wreck fish samples were mislabeled (Asensio et al, 2008). Ali, Di Taranto et al (2022) and Chen et al (2018) also did small-scale market validations of their assays on commercial samples labeled "grouper" and found that 4/4 and 3/18 samples, respectively, were mislabeled.…”
Section: Perciformesmentioning
confidence: 99%
“…Pada akhirnya metode ELISA dan imunostik akan saling melengkapi untuk mendeteksi antibodi anti A. hydrophila pada ikan mas. Beberapa aplikasi dan penelitian mengenai uji cepat imunostik yang ada saat ini adalah imunostik untuk diagnosis cepat schistosomiasis (Rossi et al, 1991), Leptospirosis pada susu (Linnode bulletin, Ireland), toksoplasmosis (Jin, et al, 2005;Subekti & Kusumastuti, 2011) diagnosis pada kasus rheumatoid arthritis (Asensio & Samaniego, 2008); serta imunostik dalam keamanan pangan yaitu mendeteksi daging ikan kerapu (grouper) yang sering dipalsukan karena bernilai ekonomis tinggi di pasaran (Hyuk et al, 2011). Berdasarkan alasan-alasan tersebut di atas, maka penelitian ini bertujuan untuk mengembangkan metode ELISA dan membuat alat deteksi cepat imunostik untuk mendeteksi antibodi anti A. hydrophila pada ikan mas.…”
Section: Pendahuluanunclassified